Subjetividades trágicas na ficção de Henry James: Daisy Miller, The Portrait of a Lady e The Wings of the Dove - Neves, Larissa Garay (2021)
Henry James virtuously narrated the society and culture of his time. A great observer of the tensions among different social registers that began to coexist more sharply during the 19th and 20th centuries, James addressed such subjects as part of his fictional and non-fictional writings. Afterwards, literary critics characterized the contrast among cultures which were discussed in his oeuvre as the “international theme”. For the fictional narratives that incorporate the subject, the author usually created European and North American characters, especially from his native country, the United States, thus producing a significant record of the social, moral, and affective characteristics of his time. Due to their unfamiliarity with European customs, but mainly due to an inaccurate reading of people and situations, American characters represented in his narratives encountered a harsh fate in contexts in which they are foreigners. Hence, the “international theme” is also considered to be the background for the creation of the tragic dimension within Jamesian fictional narratives. Therefore, this dissertation investigates how focalization integrates the tragic configuration in Henry James’s Daisy Miller, The Portrait of a Lady and The Wings of the Dove. These fictional narratives represent different writing periods of James’s career – considering the author’s narrative technique –, and therefore there are significant differences in the way the tragic is constructed, which are directly related to the focalization. In all three narratives, we discover young American protagonists traveling around the European continent. Their perspectives are excluded from the narratives during specific moments, mainly when they become distant from their true selves and there is no possible escape or salvation for them. In Daisy Miller, the tragic dimension is developed in an incipient manner. Although the story revolves around Daisy Miller, an eminent protagonist filled with avant-garde ideals, the narrative is not structured from her perspective. Nevertheless, Daisy Miller presents a rather provocative undertone: the young protagonist’s hybris could be associated to her bravery in defying society’s expectations towards her to try to assume the person she really is. From Daisy Miller to The Portrait of a Lady, an extreme change occurs within the focalization aspect in the latter novel, it directly emphasizes Isabel Archer’s subjectivity, which intensifies the tragic dimension. For this narrative, the psyche is the great tragic engine, and the protagonist’s process of recognition occurs internally, which allows the reader to understand not only the main character’s inner motivations and thoughts, but also her excruciating suffering. On the other hand, in The Wings of the Dove, the focalization focuses the perspective of three main “centers of consciousness”, and the process of unfolding the tragic is not only more complex and intense than in the previous works, but also more difficult to be understood as such. In Milly Theale’s story, there is a contemporary tragic dimension, elaborated through a narrative with almost no action, in which the process of recognition of her misinterpretations and her gradual loss of will to live occur covertly. In the end, the protagonist’s loneliness is shown through the narrative structure itself by completely excluding her as a focalizer. The narrative strategy in which the protagonists are isolated, represented by the non-narration of their perspectives, was a narratological procedure that clearly interested Henry James. During the author’s writing period, the complexity of human subjectivity being transfigured into such hermetical issues was probably still latent, and sometimes even discourse was unable to uncover them. Thus, in the above-mentioned narratives, silence is the chosen method to deal with absurd sufferings that might not get to be fully expressed through words. Therefore, we have observed innovations in the construction of the tragic dimension in Henry James’s fictional narratives: in the selected trio, the writer seems to be creating new manners to represent the tragic issues of his time, since we do not find protagonists publicly suffering in this body of work as we do in ancient tragedies or in traditional tragic narratives. The Jamesian tragic is elaborated through different methods: in Daisy Miller, The Portrait of a Lady and The Wings of the Dove, there is, either to a greater or a lesser extent, an exclusion of the tragic protagonists from the center of the narrative, which disrupts the more traditional forms of narrating the tragic dimension. Thus, Henry James develops significant changes in the creation of the tragic as he intertwines and potentializes it via the organization of focalization in his fictional narratives.